(untitled) (Shiksha Shastra Saurabh, 2025)
This study was conducted with an aim to identify the knowledge and practices of reproductive rights among women of reproductive age. Descriptive and cross-sectional methods under the quantitative research design were adopted. About 160 women from Chandragiri Municipality were selected using lottery methods. Both structured and semi-structured questionnaires were administered as the tools of data collection. The collected data were analysed and interpreted using statistical tools. A high level of awareness among the sample population was demonstrated by the fact that 84.9 % of respondents were aware of reproductive health and rights, whereas 15.1 % had never heard of them. Respondents’ perceptions of reproductive rights like making decisions which was achieved by 28.0 % and health care right was achieved by 25.1 % of respondents. Similarly, the right to information was practiced by only 19.4 % of respondents. It indicates that there are gaps in the knowledge of women’s reproductive health and access to health services in Chandragiri Municipality, which are driven by socio-economic, cultural, and gender barriers. So, accessible health services and comprehensive education in reproductive health with legal aspects should be managed both in community outreach and in school curricula effectively.